Interpretation of fi Sabilillah as One of the Zakat Recipients - Ihsan Ramadhani; Muhammad Zilal Hamzah (Universitas Darussalam Gontor, 2024)
This study discusses the interpretation of fi sabilillah as one of the groups of zakat recipients. The purpose of this study is to analyze various existing interpretations related to fisabilillah as a zakat recipient group and its application in several countries. This research uses a qualitative approach with a literature review method. Data are obtained from books, journals and fatwas from ulama forums, fatwa institutions and fiqh study institutions in several countries related to zakat, especially asnaf fi sabilillah. The results showed that there are several interpretations of fisabilillah as one of the groups of zakat recipients and the expansion of its meaning in several countries. Through the Forum of Ulama, Fatwa Institutions and Fiqh Studies Institutes in several countries, the interpretation of fisabilillah is not only limited to war but to various forms of jihad and goodness.